Mindfulness in ward nurses: A concept analysis - Xiaoyan Feng; Hongjun Zhu; Ping Cai; Yingying Zhang; Yuhong Chen (Nursing Open, 2024)
Abstract Aim Mindfulness has been widely used with all kinds of people, such as students, educators or patients. However, there have been no studies explicitly targeting ward nurses. The aim of this study is to explore the concept analysis of mindfulness in ward nurses. Design A concept analysis. Methods An electronic literature search of MEDLINE, Google Scholar, PubMed, Cambridge Online Dictionary and EBSCO on mindfulness was conducted over a ten‐year period of Peer‐reviewed scholarly articles published in English. The Walker and Avant's framework was used for this paper. Results Eleven articles in total were included in this study. Three attributes of mindfulness in ward nurses were identified as in the present moment, paying attention and being receptive. The consequence of mindfulness in ward nurses lead to positive changes, which included improving well‐being, decreased burnout, anxiety and depression. An exploration of mindfulness in ward nurses was developed. The findings of this paper can be used in ward nurses, research and administration.